2018
DOI: 10.1161/strokeaha.118.022335
|View full text |Cite
|
Sign up to set email alerts
|

Post-Thrombolysis Recanalization in Stroke Referrals for Thrombectomy

Abstract: Background and Purpose— Whether all acute stroke patients with large vessel occlusion need to undergo intravenous thrombolysis before mechanical thrombectomy (MT) is debated as (1) the incidence of post-thrombolysis early recanalization (ER) is still unclear; (2) thrombolysis may be harmful in patients unlikely to recanalize; and, conversely, (3) transfer for MT may be unnecessary in patients highly likely to recanalize. Here, we determined the incidence and predictors of post-thrombolysis ER in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 21 publications
3
55
1
Order By: Relevance
“…Several factors may explain such higher benefits from bridging for more proximal occlusions. First, occlusion site is a wellknown strong predictor of post-thrombolysis recanalization, [20][21][22] a factor strongly associated with reduced odds of early neurological deterioration 23,24 and poor outcome. 25 Second, the known higher procedural risks, including vessel perforation, with distal occlusions 26 could partly explain our finding of an association between bridging therapy and higher odds of any ICH and sICH for M2 occlusions.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may explain such higher benefits from bridging for more proximal occlusions. First, occlusion site is a wellknown strong predictor of post-thrombolysis recanalization, [20][21][22] a factor strongly associated with reduced odds of early neurological deterioration 23,24 and poor outcome. 25 Second, the known higher procedural risks, including vessel perforation, with distal occlusions 26 could partly explain our finding of an association between bridging therapy and higher odds of any ICH and sICH for M2 occlusions.…”
Section: Discussionmentioning
confidence: 99%
“…bridging vs direct mechanical thrombectomy patients will only cover patients, who had persistent occlusions on the first angiography run, or did not clinically improve after IVT, respectively. The lack of a significant difference or interaction thus does not imply that pre-interventional IVT is not beneficial in this subcohort of patients, because at least 10%–20% of patients will reperfuse before endovascular thrombectomy [46, 47], which has been associated with better clinical outcomes.…”
Section: Limitationsmentioning
confidence: 99%
“…In this study, a larger number of patients received direct thrombectomy without intravenous rtPA treatment (89.6%) than those of previous studies, as all patients had been confirmed with proximal large vessel occlusions, which are predicted to occur at significantly lower rates of thrombolytic recanalization (23). The median time of stroke onset to groin puncture, and time to reperfusion were similar to the REVASCAT trial (250 vs. 269 min and 330 vs. 355 min, respectively) (5).…”
Section: Discussionmentioning
confidence: 88%